Tech Trends. - Gassner, David; Villalobos, Ray; Rand-Hendriksen, Morten; Ritscher, Walt; Simpson, Scott (linkedin.com, 2021)
Gain clear perspectives on which up-and-coming technologies you should consider adopting and why.